Implication of guerilla marketing to consumer buying behavior: a brand awareness strategy - Suarez, Lucy G.; Rayos, Mariah Angella V.; Rongavilla, Mariah Hannah Cherlsie C.; San Agustin, Patricia Marie B.; Villaflor, Johnwell Joshua D. (b)
This study focuses on guerilla marketing as a strategic way in field of business to empower the ideation that businesses should posses. Numerous studies have cultivated that guerilla marketing provides a great impact on businesses that consist of creativity and a imaginative way of thinking. Moreover, researchers explore in-depth information that will exemplify the study that will benefit businesses to understand further about guerilla marketing. The design used in this paper is a quantitative descriptive research design to determine the recognition of guerrilla marketing and how it implicates the buying behavior of the consumer. i Three hundred ninety respondents participated in the said survey questionnaire through Google Forms which will oversee if guerilla marketing implies its consumers buying behavior. The findings determined that the hypothesis rejects the implications of guerrilla marketing on consumer buying behavior when grouped according to profile because the results are not significant at p<0.05. Thus, there is no significant difference between the groups when segmented according to age, gender, and socioeconomic status. The proponents developed ! infographic material based on the results to build brand awareness ofhow guerrillamarketing works. Lastly, the future researcher may use this study and the data to support their material for future studies regarding guerrilla 1I marketing.
Undergraduate thesis.
Keywords: guerilla marketing; consumer buying behavior; brand awareness